EU Economic Policy Priorities in the Process of Integrating European Socio-economic Models - Sankot, Ondřej, 1988-; Hnát, Pavel, 1981-; Potužáková, Zuzana, 1981-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
This thesis focuses on the identification of economic policy priorities that will allow for the intensive growth of European economies without the need for excessive fiscal or monetary stimulus inducing macroeconomic imbalances. Based on the results of the thesis, it can be stated that the main determinants of growth in the long term are the quality of institutions, which is in the European environment strongly linked to the quality of human capital and innovation capacity. However, the specific implementation of these priorities can be adapted to the specific conditions of each country. In the case of short-term growth-enhancing economic policies, states are largely given the choice of setting the priorities based on their own preferences. Scandinavian states excel in mitigating income imbalances, continental states in counter-cyclical policies and liberal model states in setting of the tax system. The identified priorities thus allow states to adapt their economic policies to a large extent to their needs, provided that national policies do not cause excessive imbalances.
Vedoucí práce: Pavel Hnát
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: evropská studia [obor disert. práce]; disertace; dissertations